2013
DOI: 10.1016/j.intimp.2013.10.019
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor effects of anti-CD40/CpG immunotherapy combined with gemcitabine or 5-fluorouracil chemotherapy in the B16 melanoma model

Abstract: Our previous studies demonstrated that anti-CD40 mAb (anti-CD40) can synergize with CpG oligodeoxynucleotides (CpG) to mediate antitumor effects by activating myeloid cells, such as macrophages in tumor-bearing mice. Separate teams have shown that chemotherapy with gemcitabine (GEM) or 5-fluorouracil (5-FU) can reduce tumor-induced myeloid-derived suppressor cells (MDSC) in mice. In this study we asked if the same chemotherapy regimens with GEM or 5-FU will enhance the antitumor effect of anti-CD40 and CpG. Us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 29 publications
(55 reference statements)
0
20
0
Order By: Relevance
“…29 Sera were collected and stored at −20°C in 100 μL aliquots. Spleen cells were harvested and rinsed in PBS for fluorescence activating cell sorter analysis.…”
Section: Xenograft Studiesmentioning
confidence: 99%
“…29 Sera were collected and stored at −20°C in 100 μL aliquots. Spleen cells were harvested and rinsed in PBS for fluorescence activating cell sorter analysis.…”
Section: Xenograft Studiesmentioning
confidence: 99%
“…Such chemotherapies as Gemcitabine and 5-Fluoruricil selectively deplete MDSC. 130,143 Small molecule inhibitors for the treatment of RCC, Sorafenib and Sunitnib, have the ability to decrease the suppressive capacity of MDSC in patients. 64,65 These agents are capable of alleviating immune suppression through altering the MDSC populations, but they possess off target effects and toxicities that can have negative effects on subsequent immune responses.…”
Section: Myeloid Derived Suppressor Cells (Mdsc)mentioning
confidence: 99%
“…[23] We searched for the mechanism accounting for the activity of 5-FU on MDSCs and found that 5-FU directly triggered MDSC cell death in vitro and in vivo. By testing the presence of activated caspases in 5-FU-treated MDSC murine cell lines, we found that 5-FU drove MDSC apoptosis in vitro, as illustrated by the presence of activated caspases 3 and 7 in 5-FU-treated MDSCs.…”
Section: -Fu Activates Immune Effectors and Eliminates Immunosuppresmentioning
confidence: 99%
“…[22] These findings were recently confirmed by Qu et al, who reported using a mouse model of B16 melanoma cancer cells growing intraperitoneally that Gem or 5-FU decreased MDSC numbers in the peritoneal cavity of tumor-bearing mice without altering the anticancer functions of mouse macrophages. [23] We searched for the mechanism accounting for the activity of 5-FU on MDSCs and found that 5-FU directly triggered MDSC cell death in vitro and in vivo. By testing the presence of activated caspases in 5-FU-treated MDSC murine cell lines, we found that 5-FU drove MDSC apoptosis in vitro, as illustrated by the presence of activated caspases 3 and 7 in 5-FU-treated MDSCs.…”
Section: -Fu Activates Immune Effectors and Eliminates Immunosuppresmentioning
confidence: 99%